Fredericella borealis Wood 2022, n. sp. - Wood, Timothy S. (Zenodo, 2022)
Fredericella borealis n. sp. (Figs 1b, e; 12a, b) Fredericella indica : Wood & Backus, 1992, p. 191, 192, fig. 6; Wood 1989, p. 21 –23, fig. 11; Wood 1991, p. 495; 2001, p. 519; 2010, p. 451; 2019, p. 524. Fredericella sultana : Rogick 1935, p. 250, 251; 1937, p. 101, 102, fig. 1B; Bushnell 1965, p. 241, 242; Økland & Økland, 2001, p. 107 –122, fig. 1C, D Holotype. NHMUK 2015.3.14.1, Fredericella borealis , collected 23 September 1994 from traveling screens, Springfield City Water, Light & Power drawing water from Springfield Lake, Springfield, Illinois, USA (in ethanol). Diagnosis. Statoblasts heavily reticulated, including areas immediately on either side of the suture, interstices about 5–6 µm in diameter. Etymology. The Latin borealis (northern) refers to the northern distribution of the species in North America and Europe, in contrast to F. indica , known so far only from the Indian subcontinent. Description. Colony appearing as narrow tubules with zooids and branches widely spaced; an early series of zooids growing along the substratum, those upright zooids later producing new series of branching tubules that may be largely free of the substratum; tubules lightly frosted to nearly opaque, with diameter of 0.18 to 0.37 mm., those along the substratum conspicuously keeled; 18–22 lophophore tentacles roughly equal in length and arranged in a circle around the mouth; statoblasts, formed within both attached and free branches, consisting of a naked capsule with no enveloping periblast; entire statoblast surface bearing a fine reticulum that extends to the suture, the reticulum more prominent on the frontal valve than the basal valve, thin vestiges of a weak attachment ring sometimes occurring on the basal valve and merging with a locally sclerotized portion of the ectocyst. Distribution. This is the dominant fredericellid in North America; it has also been reported from Germany (Massard & Geimer 1996), Japan (Hirose & Mawatari 2011a), and Norway, especially north of the Arctic Circle (Økland ...